Child passenger safety laws in the United States, 1978–2010: Policy diffusion in the absence of strong federal intervention - Bae, Jin Yung; Anderson, Evan; Silver, Diana; Macinko, James (Social science & medicine (1982), 2014)
This article examines the diffusion of U.S. state child passenger safety laws, analyzing over-time changes and inter-state differences in all identifiable features of laws that plausibly influence crash-related morbidity and mortality. The observed trend shows many states' continuing efforts to update their laws to be consistent with latest motor vehicle safety recommendations, with each state modifying their laws on average 6 times over the 30-year period. However, there has been a considerable time lag in knowledge diffusion and policy adoption. Even though empirical evidence supporting the protective effect of child restraint devices was available in the early 1970s, laws requiring their use were not adopted by all 50 states until 1986. For laws requiring minors to be seated in rear seats, the first state law adoption did not occur until two decades after the evidence became publicly available. As of 2010, only 12 states explicitly required the use of booster seats, 9 for infant seats and 6 for toddler seats. There is also great variation among states in defining the child population to be covered by the laws, the vehicle operators subject to compliance, and the penalties resulting from non-compliance. Some states cover only up to 4-year-olds while others cover children up to age 17. As of 2010, states have as many as 14 exemptions, such as those for non-residents, non-parents, commercial vehicles, large vehicles, or vehicles without seatbelts. Factors such as the complexity of the state of the science, the changing nature of guidelines (from age to height/weight-related criteria), and the absence of coordinated federal actions are potential explanations for the observed patterns. The resulting uneven policy landscape among states suggests a strong need for improved communication among state legislators, public health researchers, advocates and concerned citizen groups to promote more efficient and effective policymaking. •We examined the adoption trend of three major child passenger safety laws of 50 states in the U.S. from 1978 to 2010.•The results show that diffusion of child passenger safety policies occurred even without strong federal intervention.•However, there is a long time lag between the publication of scientific knowledge and its incorporation into state laws.•There is wide state-to-state variation in defining who should comply, what action is required and what the penalties are.•Complexity of the science, changing guidelines, and the absence of coordinated federal action are potential explanations.